Structural racism in school contexts and adolescent depression: Development of new indices for the National Longitudinal Study of Adolescent to Adult Health and beyond - Jessica A. Polos; Stephanie M. Koning; Taylor W. Hargrove; Kiarri N. Kershaw; Thomas W. McDade (Elsevier, 2022)
Racial discrimination is an important predictor of racial inequities in mental and physical health. Scholars have made progress conceptualizing and measuring structural forms of racism, yet, little work has focused on measuring structural racism in social contexts, which are especially relevant for studying the life course consequences of racism for health. Using the National Longitudinal Study of Adolescent to Adult Health, we take a biosocial, life course approach and develop two life stage-specific indices measuring manifestations of structural racism in school contexts in adolescence, a sensitive period of development. The first is a school contextual disadvantage index (CDI), which captures differences in resources and opportunities across schools that have been partly determined by socio-historic structural racism that has sorted Black students into more disadvantaged schools. The second is a school structural racism index (SRI), which measures differences in resources and opportunities between Black and white students within schools. Then, we relate these indices to adolescent depressive symptoms. We find that among both Black and white students of both genders, higher CDI levels are associated with more depressive symptoms. However, Black students are twice as likely to be in schools with a CDI above the median compared to white students. We also find that, controlling for the CDI, the SRI is positively associated with depressive symptoms among Black boys and girls only. Finally, the CDI and the SRI interact to produce a pattern where the likelihood of depressive symptoms increases as the SRI increases, but only among Black boys and girls in low-disadvantage schools. These findings underscore the importance of measuring structural racism in social contexts in multifaceted ways to study life course health inequities.